A new species of Prorops Waterston 1923 (Hymenoptera: Bethylidae) from Cambodia with a key to world species - Lim, Jongok; Lee, Seunghwan (Zootaxa, 2011)
Prorops Waterston 1923 can be easily distinguished from the other genera of Sclerodermini (Bethylidae: Epyrinae) mainly by having frontal process of head well-developed; antenna twelve segmented; median, basal, and anal veins absent (Evans 1978; Terayama 2006).